Al-rich AlGaN Alloys: Unique Materials for Deep UV LEDs - Nakarmi, Mim Lal (Journal of Nepal Physical Society, 2023)
Energy bandgap of AlxGa1−xN alloys can be tuned systematically from ∼ 3.4 to 6.1 eV by changing the alloy composition (x) from 0 to 1 and the direct bandgap nature is maintained in the entire range of alloy compositions which make the AlGaN alloys suitable materials for the development of light emitting diodes (LEDs) covering the ultraviolet (UV) spectral region from 210 to 400 nm. For LEDs in the deep UV regions (λ < 300 nm), Al-rich AlGaN alloys of Al content higher than 50% are required. Deep UV LEDs have applications in a wide range of fields including display, disinfection, medical, sensing, and communication. With recent progress in the material growth and electrical conductivity, Al-rich AlGaN alloys have emerged as unique wideband gap materials for the development of deep UV LEDs. In this review article, how the progress of Al-rich AlGaN alloys has made in terms of the material growth and electrical conductivity leading its emergence as deep UV materials have been reviewed. Challenges and prospects of the deep UV LEDs to improve the performance of the devices will also be discussed.